SRDP: Secure Route Diversion Policy for Resisting Illegitimate Request in MANET - C Ramaprasad, H; C Lingareddy, S (International Journal of Engineering and Technology, 2018)
Optimized Link Source Routing (OLSR) is currently identified as one of the robust on-demand protocol in Mobile Adhoc Network (MANET) for offering good communication performance. However, there are very less evidence where it is found to support potential security. After reviewing existing security approaches in MANET, it is found that there is a still an open scope of security in MANET where the potential of OLSR can be harnessed. Hence, this manuscript presents SRDP or Secure Route Diversion Policy that is capable of identifying the incoming threat irrespective of any form of attacks. SRDP allows comprehensive identification of threat and it offers safety to the network by further resisting such incoming messages to be propagated within its secured network. The study outcome shows that SRDP offers good communication performance and retain good balance with cost effectiveness in contrast to existing security schemes.Â Â